Assessment of Language Functions in Patients With Disorders of Consciousness Using an Alternative Communication Tool - Kujawa, Katarzyna; Zurek, Grzegorz; Kwiatkowska, Agnieszka; Olejniczak, Roman; Żurek, Alina (Frontiers in Neurology, 2021)
This study aimed to describe the percentage of tasks involving language functions that were completed by patients diagnosed with disorders of consciousness, as observed during neurorehabilitation conducted for different periods of time using an alternative communication tool. The project involved six participants, who were observed for 1 month, 6 months, and 1 year. The patients were asked to solve tasks involving language functions with the use of an eye-controlled device. The language functions were evaluated on the basis of the average number of tasks performed by the patients, which was 70.45% for the whole subject group. It is not entirely clear what determined the changes in language functions during the research. It is crucial that patients performed the presented tasks even though their state of consciousness, as confirmed through medical documentation (unresponsive wakefulness syndrome), did not suggest the possibility of establishing any contact with them.